Auditing in the food industry : from safety and quality to environmental and other audits - Dillon, M.; Griffith, C. J. 1946- (Woodhead Publishing in food science and technology., 2001)
The food industry currently faces an unprecedented level of scrutiny. Consumers are concerned not just about the safety and quality of food products but also the way in which they are produced. At the same time the industry has developed new ways of assuring appropriate standards for its products and their methods of production, developing systems such as TQM and HACCP to identify and manage key steps in production. Auditing in the food industry provides an authoritative guide to the range of standards and audits now being used.